Florística e fitossociologia de fragmentos em área ecotonal Cerrado-Pantanal no município de Santo Antônio do Leverger - Mato Grosso - Oliveira, Oacy Eurico de (2011)
The present study aimed to evaluate the floristic features and the phytosociology of the trees and shrubs in fragments from an ecotonal area in the cerrado and pantanal biomes, in the municipality of Santo Antonio of Leverger-MT. The study was carried out in two areas considering the geography of the study site: area I (RM), including the head stream of the Mortes river, the Cerrado biome, Araguaia Basin and cerrado sensu stricto, and area II (RC) including the head stream of the Caeté river, the Pantanal biome, Prata Basin, and cerrado sensu lato. All individuals with CAP > 15.00 cm (1.30 m above the ground) were surveyed in 50 plots of 20 x 20 m which composed a sample area of 2.0 ha. The diversity indexes of Shannon, Simpson, and Pielou were used to evaluate the diversity and the Quotient of mixture of Jentsch was used to evaluate the dispersion. A total of 1,443 individuals were evaluated, distributed in 78 botanical families, 134 genera, and 161 species; two families and two species were indeterminate and unidentified, respectively. Thirty two families (41%) and 49 species (30.5%) were common to both areas. Thirty seven families, 61 genera, 77 species, one undetermined family, and one unidentified species were observed in area I (RM). The more significant families considering the number of species were Leguminosae (12 species), Annonaceae and Sapotaceae (5 species each), Apocynaceae, Cecropiaceae, and Myrtaceae (4 species each), and Burseraceae, Melastomataceae, Moraceae, and Rubiaceae (3 species each). The obtained indexes of Shannon, Simpson, and Pielou, and Quocient of mixture of Jentsch were 3.81; 0.030; 0.87; and 0.111, respectively. These indexes evidenced a community with high diversity and uniformity. The area presented a density of 695 individuals/ha and basal area of 20.3 m2 /ha. Forty one families, 73 genera, 84 species, one undetermined family, and one unidentified species were observed in area II (RC). The more significant families considering the number of species were Leguminosae (15 species), Annonaceae, Euphorbiaceae, Moraceae, and Rubiaceae (4 species each), and Cecropiaceae, Combretaceae, Lauraceae, Myrtaceae, and Sapotaceae (3 species each). The obtained diversity and dispersion indexes of Shannon, Simpson, and Pielou, and the Quocient of mixture of Jentsch were 3.74; 0.035; 0.84; and 0.111, respectively, demonstrating the presence of a community with a high level of diversity. The area presented a density of 748 individuals/ha and a basal area of 29.3 m2 /ha. The similarity analysis by the index of Jaccard (SJ) for the total area was 0.5, confirming the presence of high floristic similarity.